Respiratory infections in elderly people: Viral role in a resident population of elderly care centers in Lisbon, winter 2013–2014. (April 2018) - Chasqueira, Maria-Jesus; Paixão, Paulo; Rodrigues, Maria-Lúcia; Piedade, Cátia; Caires, Iolanda; Palmeiro, Teresa; Botelho, Maria-Amalia; Santos, Madalena; Curran, Martin; Guiomar, Raquel; Pechirra, Pedro; Costa, Inês; et al.
Highlights: An etiological agent was found in 60% of the acute respiratory infections. Human metapneumovirus showed an association with severe infection. The importance of atypical bacteria in severe cases, in particular L. pneumophila. The low effectiveness of the influenza vaccine. Abstract: Objective: The aim of this study was to analyze the etiology and clinical consequences of viral respiratory infections in 18 elderly care centers (ECC) in Lisbon, which housed a total of 1022 residents. Methods: Nasopharyngeal swabs were collected whenever an elderly had symptoms of acute respiratory infections (ARI). PCR and RT-PCR were performed for influenza A/B, human parainfluenza virus 1–4, adenovirus, human metapneumovirus (HMPV), respiratory syncytial virus (RSV), rhinovirus, enterovirus, human coronavirus and human Bocavirus (HBoV). Array cards for atypical bacteria were also used in severe cases. Results: In total, 188 episodes of ARI were reported, being rhinovirus the most frequently detected (n = 53), followed by influenza A(H3) (n = 19) and HBoV (n = 14). Severe infections were reported in 19 patients, 11 of which were fatal, Legionela pneumophila, rhinovirus, HMPV and RSV associated with these fatalities. Nine influenza strains were analyzed, all antigenically dissimilar from vaccine strain 2013/14. "Age", "HMPV" and "Respiratory disease" showed an association with severe infection. Conclusions: In this study an etiologic agent could be found in 60% of the acute respiratory episodes. These data provides information about the circulating viruses in ECC and highlights the importance of searching both viruses and atypical bacteria in severe ARI.